Diabetes, obesity, metabolism, and SARS-CoV-2 infection: the end of the beginning - Drucker, Daniel J. (Cell metabolism, 2021)
The increased prevalence of obesity, diabetes, and cardiovascular risk factors in people hospitalized with severe COVID-19 illness has engendered considerable interest in the metabolic aspects of SARS-CoV-2-induced pathophysiology. Here, I update concepts informing how metabolic disorders and their co-morbidities modify the susceptibility to, natural history, and potential treatment of SARS-CoV-2 infection, with a focus on human biology. New data informing genetic predisposition, epidemiology, immune responses, disease severity, and therapy of COVID-19 in people with obesity and diabetes are highlighted. The emerging relationships of metabolic disorders to viral-induced immune responses and viral persistence, and the putative importance of adipose and islet ACE2 expression, glycemic control, cholesterol metabolism, and glucose- and lipid-lowering drugs is reviewed, with attention to controversies and unresolved questions. Rapid progress in these areas informs our growing understanding of SARS-CoV-2 infection in people with diabetes and obesity, while refining the therapeutic strategies and research priorities in this vulnerable population. COVID-19 infection produces excess mortality in people with obesity or diabetes. Here we review the epidemiology, susceptibility to infection, pathophysiology, immunology, complications, potential therapeutic options, and response to vaccinations in people with metabolic disorders and SARS-CoV-2 infection.